An integrated thermoelectric heating-cooling system for air sterilization— a simulation study. (July 2021) - Ji, Rencai; Pan, Teng; Peng, Guilong; Ma, Jianqiang; Yang, Nuo; Hao, Qing
Abstract: Semiconductor thermoelectric devices are broadly used for various heat-pump applications, where they function as either a heater or a cooler. In this article, an integrated system combining thermoelectric heating and cooling is introduced, which not only improves the overall energy efficiency but has a great potential for applications in air sterilization and purification. In the proposed system, the air is firstly heated up for air sterilization by fins thermally grounded to the hot side of multiple thermoelectric devices. The air is then cooled down by the cold side of the same thermoelectric devices. The heat exchange and flow conditions of the system are analyzed, and it is found that the Nusselt number ratio after adding the fins is increased by two times compared with the smooth tube. The air temperature in the system can reach up to more than 65°C using multiple thermoelectric devices. Such a temperature is able to inactivate many viruses. The coefficient of performance of the overall system can reach 5.4. This work demonstrates new applications of thermoelectric devices for energy-efficient air sterilization applications. Graphical abstract: An integrated air sterilization system combining thermoelectric heating and cooling is introduced. The air temperature in the system can reach up to more than 65 °C, and can be cooled to 40 °C after passing through the cold side. The value of COP∗ is about 5.4. Image 1 Highlights: An integrated air sterilization system combining thermoelectric heating and cooling is introduced. The system can simultaneously realize thermal sterilization (more than 65 °C) and air cooling. The coefficient of performance of the overall system can reach 5.4. Choosing a material with a large ZT (1.7) value has a higher COP value (7.8) and a higher hot side temperature (more than 80 °C).